An analysis of the economic effects of improper electronic data interchange methods at a small company - Garlick, Cynthia (Kansas State University, 2022)
The purpose of this study is to provide insight into the financial implications of inefficient implementation of electronic data interchange (EDI) systems for the use of processing electronic customer orders, as well as discuss why proper EDI adoption is critical. The specific objective of this study is to estimate the annual cost of improper use of EDI based on employee time spent manually entering orders that are received via EDI transmission. The estimated costs are used to calculate net present value (NPV) over the life of the investment in technology for up to a 10-year time frame. The findings provide organizations who currently use EDI systems, or are looking to adopt, with the information necessary for (a) efficient implementation to obtain the largest cost savings and benefits possible and (b) determining the cost-effectiveness of investments in employee trainings on EDI use. Primary data was collected for this study from one specific firm which was determined to be using inefficient EDI practices, lowering their return on investment (ROI) in this technology. The data referenced salaries, time and cost estimates obtained from professionals at the firm. After the primary data was collected and converted to dollars, a financial analysis was projected over a 10-year time frame. The NPV of the cumulative expenses incurred from inefficient EDI implementation was calculated using a five percent discount rate to estimate the benefit the firm could gain by investing in improving the efficiency of EDI use. The results show that inefficient EDI implementation decreases the expected ROI from the initial investment. If the firm continues their inefficient methods, they can stand to lose at least $143,710 over five years and $206,434 over ten years. It is in the firm’s best interest to change their methods, invest in training, and adopt better practices. For further research, it would be beneficial to conduct an in-depth analysis on all inefficient EDI practices, instead of only order entry processes. Data should also be collected to analyze the emotional cost endured by employees that experience burnout and job dissatisfaction as a direct result from inefficient implementation. The findings in this study, and future research, will guide organizations to use proper techniques from the point of implementation so that they can maximize the benefits of EDI in improving operational efficiency.
Keywords: Electronic data interchange; Economic effects; Agribusiness; Efficiencies